PENGARUH KEKUASAAN POLITIK TERHADAP PEMBENTUKAN HUKUM DI INDONESIA - NURAINI, NURAINI (Jurnal Hukum Volkgeist, 2018)
The state of Indonesia embraces the sovereighty of the people or democracy. The people are the owners of the highest power in the state. The real power comes from the people, by people, and for the people. Even idealized power is held together with the people. Indonesia itself is also a country that adheres to the law. From the opinion of the exparts we can see that the state that follows the rule of law is always related to power. Where power is always limited by the laws that bind it. In other words the sphere of power is limited by the rules that are bound by the rules that have been composed and written and made by the agency that is authoorized to make it.The type of research used is normative juridical research. This study uses “ conceptual approach, legislation approach, and historical approach, in discussing the problems that exist in this research method is a way to perform analysis of data.Political power is the ability to use the source of influence to influence the process of making and executing political decisions so as to benefit itself, the group or society in general. Power is a gekala that always exist in the political process, in Indonesia law is a product of power (politics) so that the character of each legal product  will be determined or colored by consideration of force political configuration that gave birthday.